Successful CAR-T cell therapy in a refractory MCL patient with bacterial, fungal and COVID-19 infection: a case report - Radici, Vera; Giagulli, Cinzia; Accorsi Buttini, Eugenia; Farina, Mirko; Polverelli, Nicola; Brugnoni, Duilio; Chiarini, Marco; Galvagni, Anna; Almici, Camillo; Ferrari, Emilio; Bianchetti, Andrea; Masneri, Stefania; et al. (Frontiers in Transplantation, 2023)
Background The COVID-19 pandemic has had a significant impact on the management and care of onco-hematological patients, particularly those with lymphoproliferative disorders who are at higher risk for COVID-19 associated bacterial and fungal superinfections. Case presentation We present the successful treatment of a 44-year-old male patient with refractory mantle cell lymphoma treated with chimeric antigen receptor T (CAR-T) cell therapy, despite concurrent COVID-19 infection. The patient developed grade II cytokine release syndrome, requiring admission to the intensive care unit. The CAR-T cells expanded effectively, and the patient achieved complete metabolic remission. During the treatment course, the patient experienced complications including COVID-19-associated pulmonary aspergillosis and a co-infection with Stenotrophomonas maltophilia and the SARS-CoV-2 omicron variant. Prompt antifungal and antibacterial therapy, along with appropriate COVID-19 treatment, led to the resolution of these infections. Dexamethasone was also administered to reduce inflammation and aid hematologic recovery. Despite the presence of multiple infections, the patient achieved complete remission of lymphoma, highlighting the effectiveness of CAR-T cell therapy in this high-risk patient. Conclusion Despite the challenges posed by concurrent infections, the decision to proceed with CAR-T cell therapy in this patient proved to be successful, resulting in complete remission of lymphoma. Early initiation of supportive therapies and the use of dexamethasone contributed to the resolution of complications. This case underscores the importance of individualized decision-making and the potential benefits of CAR-T cell therapy in similar high-risk patients.